Corpo, gênero e sexualidade em um livro didático de Ciências da Natureza do PNLD/EJA 2014 - Marques, Youry Souza (2021)
What and how body, gender and sexuality are discussed in the disciplinary components of the Natural Sciences area of the didactic collection for EJA - High School approved by PNLD/EJA - 2014? That was the guiding question of the dissertation carried out in the scope of the Education in Science and Mathematics Research Line, of the Graduate Program in Education at the Federal University of Uberlândia. Thus, the general objective was outlined: To analyze the sayings about body, gender and sexuality present in the disciplinary components of the Natural Sciences area of a didactic collection approved by PNLD/EJA 2014. As specific objectives: (i) Identify the sayings and unspoken about body, gender and sexuality in the analyzed book (ii) Describe the way in which bodies, genders and sexualities are presented by written texts and images located in the disciplinary components of the Natural Sciences area. The theoretical contribution of this research is based on the theoretical field of Cultural Studies in its strand in dialogue with critical and post-critical theoretical-epistemological fields, as well as with some precepts of Foucault's theories of gender and education. From the standpoint of methodology, it is characterized as a qualitative approach to research, using Cultural Analysis and document analysis. Hence, the textbook, recognized by us in its multiplicity, was taken as a cultural artifact and as a document. Therefore, we chose the textbook that contains the discipline components of Nature Sciences of EJA - High School approved by PNLD/EJA - 2014 as a research source, adopted in Brazilian public schools and accessed in the libraries of these institutions. The book is addressed to a specific student audience, inserted in the job market or in search of greater professional qualification, the language utilized naturalizes the generic male. The book addresses different professions, occupations and jobs, characterizing the relationship between the public and private spheres, images of men in plural contexts of work exercises and those of women described at home or in the health area. In this investigative examination, we note that there is an evident positioning of the subjects based on the demarcations built on the expectation of sex-body-gender and work. When carrying out analyzes considering the body as the material basis for the intertwining of gender, race/ethnicity and life stages, we found that the images of adult white men are numerically greater than any other. The discussion on sexuality is mostly located in the Biology component, presented from a biomedical perspective, linked to the themes of sex, HIV/AIDS, condoms, hormones and sexual human reproduction, strongly built on binary and heterosexual logic. On the other hand, we face some resistance in specific places, which present plural teachings about the body, gender and sexuality, highlighted, to a large extent, in the complementary texts of the textbook.